Application of physiotherapeutic methods to support training and post-exercise recovery of combat sports and martial arts contestants - Boguszewski, D. (Journal of Combat Sports and Martial Arts, 2015)
Introduction. High-performance training does not only constitute physical effort, but also a number of supporting psychological, medical and physiotherapeutic activities. The purpose of this study was to characterize physiotherapeutic methods applied in supporting training and biological regeneration of athletes of martial sports and arts. Materials and methods. 149 athletes of judo, aikido, kickboxing and taekwondo participated in the survey. The author`s survey constituted the study tool. Differences were calculated using the chi-squared and t-Student test for independent groups, assuming p=0.05 as the minimum significance level. Results. Regular use of physiotherapy treatments supporting trainings and post-exercise regeneration was declared by 103 (69%) of the studied athletes (75% judo athletes, 26% aikido athletes, 65% kickboxing athletes and 70% taekwondo athletes). Selection of treatments was diverse (p<0.05), but the most frequently applied treatment indicated by representatives of all disciplines was sauna. Regular use of complementary exercises was declared by 123 (83%) studied athletes (84% judo athletes, 62% aikido athletes, 88% kickboxing athletes and 93% taekwondo athletes). No significant differences were observed regarding the selection of complementary physiotherapeutic exercises among representatives of various disciplines. Among complementary exercises the studied athletes did stretching most frequently (44%). Conclusions. 1. The most commonly used physiotherapy treatments include the ones which are easily accessible (sauna, taping, massage). Nonetheless, their effectiveness is scientifically proven. 2. Among treatments and exercises used by athletes there are modern forms, such as kinesiotaping or stabilizing exercises, which show professionalism of coaches and sports physiotherapists.